(untitled) (Research, Society and Development, 2021)
Four pâté formulations were developed using the tilapia fillet residue with the addition of oregano oil: control without oil addition; 0.03%; 0.06% and 0.09% oil. Analyzes of centesimal composition, pH, aw, color and lipid oxidation (TBARS) were performed. All samples were in accordance with Brazilian legislation for physical-chemical standards and showed a decrease in pH during the storage period under refrigeration. There was no significant difference in the L* and the values ​​of a* showed a decrease during storage. Regarding lipid oxidation, the sample 0.09% was similar to the control. In this sense, it is concluded that the production of pâté with the addition of oregano oil may be an alternative for the use of the waste from the tilapia processing industry.